TECHNIQUE OF THE CHOICE OF SOFTWARE PRODUCTS STRUCTURE ON THE BASIS OF MODERN STANDARDS OF RESOURCE MANAGEMENT IN CORPORATE INFORMATION SYSTEMS - Самков, О. В.; Захарченко, Ю. А.; Степанюк, О. А. (Science-based technologies, 2011)
In this article is formulated and solved the problem of comparative evaluation and selection of the best options for the software of modern standards of resource management MRP / ERP for corporate information systems and develop a method.